HUBUNGAN NYERI TERKAIT ENDOMETRIOSIS DENGAN KUALITAS KEHIDUPAN SEKSUAL PADA PEREMPUAN USIA REPRODUKSI - Setiawan, Gilbert Wendy; Mamengko, Linda; Kumaat, Toar (JURNAL KEPERAWATAN, 2026)
Background : Endometriosis adversely affects the sexual quality of life of women of reproductive age. The role of endometriosis-associated pain in female sexual dysfunction remains incompletely understood. Objective : To assess the relationship between endometriosis-associated pain and sexual quality of life in women of reproductive age. Methods: A cross-sectional study was conducted at Prof. R.D. Kandou Hospital in 2025 among women aged 18–47 years with surgically confirmed endometriosis. Female sexual dysfunction was assessed using the female sexual function index. Bivariate analyses were performed to compare demographic characteristics and female sexual function index domains between women with and without sexual dysfunction. Results: Eighty-five participants were included, of whom 70.6% were classified as having female sexual dysfunction. The mean index score was 24.24 ± 2.34. Significant differences were observed in arousal, lubrication, orgasm, satisfaction, and pain domains (p < 0.001). Body mass index was also significantly associated with female sexual dysfunction (p < 0.001), whereas other demographic variables and the desire domain were not. Conclusion: Female sexual dysfunction is highly prevalent among women with endometriosis and is associated with impairments across multiple domains of sexual function. Management strategies should address sexual health comprehensively and not be limited to pain control alone. Keywords: Endometriosis; female sexual dysfunction; female sexual function index